The CEMA method in the compensatory classroom (Journal of Parents and Teachers, 2023)
The CEMA method, consisting of four stages in a logical and unalterable order: Understand – Enunciate – Memorise – Apply, is based both on the in-depth observation of children and their learning processes, and on the study and deepening of knowledge and scientific knowledge. It shows us, as teachers, the steps to take to provoke the knowledge of the learner from the respect for diversity, including all our students, seeking as a result the integral development of the person.
Keywords: learning; understand; diversity; comprehensive; development respect